2015
DOI: 10.1136/tobaccocontrol-2014-052084
|View full text |Cite
|
Sign up to set email alerts
|

Has the introduction of plain packaging with larger graphic health warnings changed adolescents’ perceptions of cigarette packs and brands?

Abstract: ObjectiveTo examine the impact of plain packaging of cigarettes with enhanced graphic health warnings on adolescents’ perceptions of pack image and perceived brand differences.MethodsCross-sectional school-based surveys conducted in 2011 (prior to introduction of new cigarette packaging) and in 2013 (7–12 months afterwards). Students aged 12–17 years (2011 n=6338; 2013 n=5915) indicated whether they had seen a cigarette pack in previous 6 months. Students rated the character of four popular cigarette brands, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 22 publications
9
50
1
Order By: Relevance
“…Other survey work with adolescents (again not necessarily smokers) has shown shifts over time in pack perceptions, brand image, and beliefs of harmful consequences due to a combined presentation of the GWHs and plain packs 44 45. Our experimental study across three different countries focuses on two key outcomes from GHWs and plain packs—that is, short-term cigarette craving21 and longer-term thoughts of quitting 22.…”
Section: Introductionmentioning
confidence: 99%
“…Other survey work with adolescents (again not necessarily smokers) has shown shifts over time in pack perceptions, brand image, and beliefs of harmful consequences due to a combined presentation of the GWHs and plain packs 44 45. Our experimental study across three different countries focuses on two key outcomes from GHWs and plain packs—that is, short-term cigarette craving21 and longer-term thoughts of quitting 22.…”
Section: Introductionmentioning
confidence: 99%
“…A promising strategy is the introduction of standardised tobacco packaging or plain packaging by the Norwegian Ministry of Health and Care Services in 2015. 17 It is suggested that the introduction of mandatory plain packaging for tobacco products would: reduce the attractiveness of tobacco products; 18,19 increase the noticeability of health warnings and messages; 20 and reduce smokers' misperceptions about the harmfulness of tobacco products as pack branding features such as colours are used to convey messages of reduced harm, such as lighter pack colours used to signify 'light' cigarettes. 21 Studies in Australia, the first country to introduce plain packaging in 2012, showed that the introduction of plain packaging of cigarettes coupled with larger graphic health warnings has reduced the appeal of smoking among adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…21 Studies in Australia, the first country to introduce plain packaging in 2012, showed that the introduction of plain packaging of cigarettes coupled with larger graphic health warnings has reduced the appeal of smoking among adolescents and adults. 6,19 Plain packaging also contributes to making the image of smoking less positive which has the potential to reduce smoking uptake among adolescents. 22 In addition, harm reduction strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…8−10 Australian regulatory changes that increased the size of graphic health warnings and introduced plain packaging are reducing cigarette pack appeal among adolescents 11 , and recent regulatory changes further restricting tobacco advertising, promotion and sponsorship at the point of sale have also helped to reduce smoking among Australian adolescents.…”
Section: Nonprice Measures To Reduce the Demand For Tobaccomentioning
confidence: 99%